SCOPE OF SNBL PLATFORMS AND THEIR ROLE IN ESCALATING THE FINANCIAL INDEPENDENCE OF ITS USERS - Dr. Sarita Rana; Aryan Jain; Pranav Sehgal; Vikramjeet Singh Sandhu (Innovative Research Thoughts, 2023)
This research paper aims to explore the global and domestic scope of "Save Now, Buy Later" (SNBL) apps/platforms and their role in enhancing the financial independence of individuals who adopt these services. SNBL apps have gained significant popularity in recent years, offering consumers the ability to save towards a purchase and defer the payment to a later date. The study investigates the impact of SNBL platforms on consumer behaviour, financial decision-making and overall financial independence. Additionally, it analyses the potential benefits and risks associated with these platforms, taking into account both global and domestic perspectives. The research employs a mixed-method approach, combining qualitative interviews with SNBL users and quantitative analysis of relevant data and financial indicators. The findings provide valuable insights for policymakers, financial institutions, and consumers, contributing to a comprehensive understanding of the SNBL phenomenon and its implications for personal financial management.